High-performance PPO / POK alloy material as well as preparation method and application thereof
By preparing PS-g-POK resin in PPO/POK alloy materials, the compatibility and performance of the alloy are improved, the problem of insufficient performance of existing alloys is solved, and higher strength, toughness and heat resistance are achieved, which broadens its application areas.
Patent Information
- Application Number
- CN202510330922.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-20
AI Technical Summary
The existing PPO/POK alloy materials have poor performance, difficult processing, insufficient heat and chemical resistance, and poor mechanical properties.
By performing bromine reaction on the POK resin and styrene graft polymerization, PS-g-POK resin is prepared and blended with the PPO resin to improve the compatibility and performance of the PPO/POK alloy.
It improves the compatibility, strength, toughness, chemical resistance, heat resistance and wear resistance of PPO/POK alloy, solves the problems of processing difficulties and insufficient performance, and broadens its application in automotive instrument panels, pipelines, valves, gears and bearings.
Smart Images

Figure CN119842208A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a high-performance PPO / POK alloy material and a preparation method and application thereof. Background Art
[0002] Polyphenylene ether (PPO for short) is one of the five major engineering plastics containing phenoxy groups on the main chain of the molecule. The main chain is composed of benzene rings and oxygen atoms. It has excellent properties such as high heat resistance, high dielectric properties, acid and alkali resistance, and hydrolysis resistance. It is widely used in electronics, home appliances, office automation, automotive industry, aerospace, and military industries. It is used as materials for automotive dashboards, fenders, printed circuit boards, pipes, valve corrosion-resistant parts, gears, and bearings.
[0003] However, the rigidity of the main chain structure of PPO molecules leads to a high melting point, high melt viscosity, poor fluidity, and thus difficulty in processing. In addition, it has the disadvantages of poor solvent resistance, easy stress cracking of products, and low notch impact strength. The high processing temperature (330°C) of PPO is prone to degradation, resulting in difficulties in processing and excessive energy consumption. In order to overcome these shortcomings and give PPO new properties, a variety of modification methods have been carried out on it. Generally, polystyrene (PS) is used for modification to improve the processing fluidity of the alloy. Researchers continue to study PPO alloying, modifying engineering plastics such as polyamide (PA), polybutylene terephthalate (PBT) and polyphenylene sulfide (PPS) with PPO to develop the second generation of polyphenylene ether alloys.
[0004] PPO and PS are both amorphous polymers with good compatibility. By mixing PS, the processing cost can be reduced and the processing formability of PPO can be greatly improved, but the heat resistance is reduced. The blending modification of PPO and PA not only improves the processing performance and solvent resistance of PPO, but also improves the heat resistance and dimensional stability of PA, thus achieving complementary advantages. However, the compatibility of the two is very poor, belonging to a completely incompatible system. The phase separation of the blended alloy is serious, resulting in the brittleness of the alloy. It is necessary to increase the capacity and toughness of the PPO / PA alloy to meet the application requirements. However, the PPO / PA alloy still has the problem of high water absorption.
[0005] Polyketone (POK) resin is a new type of green, environmentally friendly, thermoplastic engineering plastic. It uses carbon monoxide, ethylene and propylene as the main raw materials. It has low water absorption, high wear resistance, high chemical resistance, high impact strength and high gas barrier properties. Its wear resistance is 14 times that of polyoxymethylene (POM), its impact toughness is 2.5 times that of PA6, and its oil resistance is 2 times that of PA12. It is almost the most balanced engineering material at present, with very broad application prospects and rapid development. At present, there are some reports on PPO / POK alloys. The patent with application number 201810179218.6 reports on polyphenylene ether / polyketone flame-retardant composite materials and their preparation methods. PPO / POK is melt-blended and modified by adding compatibilizers and flame retardants. The material has excellent flame retardant properties and can achieve 5VA flame retardant properties, but the mechanical properties are greatly reduced. Patent application number 202311362291.4 reports a method for preparing a low dielectric PPO / POK alloy, using linear non-oil-filled styrene-ethylene-butylene-styrene block copolymer (SEBS) and linear oil-filled SEBS to toughen and modify the alloy, but this also results in a decrease in the modulus of the alloy. In addition, due to the high viscosity of the PPO resin, the fluidity of the prepared alloy is poor. Summary of the invention
[0006] One of the purposes of the present invention is to provide a high-performance PPO / POK alloy material to solve the problem of poor performance of existing PPO / POK alloys; The second object of the present invention is to provide a method for preparing a high-performance PPO / POK alloy material; A third object of the present invention is to provide an application of a high-performance PPO / POK alloy material.
[0007] The purpose of the present invention can be achieved through the following technical solutions: In a first aspect, the present invention provides a high-performance PPO / POK alloy material, comprising the following components in parts by weight: PPO resin 50-80 parts; PS-g-POK resin 5-20 parts; 5-20 parts of POK resin; Antioxidant 0.1-1 part; Lubricant 0.1-1 part.
[0008] As a further embodiment of the present invention, the PS-g-POK resin is prepared by the following steps: S1. Caprolactam dissolution: Using CPL (caprolactam) as a solvent, dissolve POK resin in CPL at a temperature of 135-145°C, mix well, and obtain a POK / CPL solution; S2. Bromination reaction grafting: under nitrogen and stirring conditions, add a strong base solution to the POK / CPL solution and react at 135-145°C for 2-4 hours; then add 4-bromostyrene solution and continue to react for 5-7 hours to obtain an intermediate product; S3. Styrene graft polymerization: Add AIBN (azobisisobutyronitrile) and styrene to the intermediate product at a temperature of 95-105°C and nitrogen, stir and react for 7-9 hours, collect the product, and obtain PS-g-POK resin after drying.
[0009] As a further solution of the present invention, in S1, the mass ratio of POK resin to CPL is 10:90.
[0010] As a further solution of the present invention, in S2, the concentration of the strong base solution is 0.1 M, and the strong base is any one of potassium tert-butoxide (tBuOK) and sodium ethoxide.
[0011] As a further solution of the present invention, in S2, the mass ratio of POK to strong base in the POK / CPL solution is 10:1.
[0012] As a further embodiment of the present invention, in S2, the mass ratio of POK to 4-bromostyrene in the POK / CPL solution is 1:2.
[0013] As a further embodiment of the present invention, in S2, the concentration of the 4-bromostyrene solution is 0.5 M, and the solvent of the 4-bromostyrene solution is ethanol or dimethyl sulfoxide.
[0014] As a further solution of the present invention, in S2, the stirring speed is 50-100 r / min.
[0015] As a further solution of the present invention, in S3, AIBN is used as an initiator, and the mass ratio of AIBN to POK in the intermediate product is 0.01-0.1:1.
[0016] As a further embodiment of the present invention, in S3, the mass ratio of styrene to POK in the intermediate product is 0.1:1.
[0017] As a further embodiment of the present invention, in S3, the product is precipitated with a mixed solvent of water and ethanol (V / V=1:1), filtered, washed, and then dried in vacuo at 60°C.
[0018] As a further embodiment of the present invention, the POK resin is one of a carbon monoxide-ethylene binary copolymer or a carbon monoxide-ethylene-propylene terpolymer, wherein the amount of propylene in the terpolymer is less than twice that of ethylene.
[0019] As a further embodiment of the present invention, the antioxidant consists of antioxidant 1010 and antioxidant 168.
[0020] As a further embodiment of the present invention, the lubricant is ethylene bisstearamide (EBS).
[0021] In a second aspect, the present invention provides a method for preparing a high-performance PPO / POK alloy material, comprising the following steps: The components are weighed according to their weight proportions, blended and modified by a twin-screw extruder, and dried after cooling, cutting, granulation, to obtain a PPO / POK alloy material.
[0022] As a further solution of the present invention, the feeding section temperature of the twin-screw extruder screw is 200°C, the compression section temperature is 200-220°C, the metering section temperature is 220-240°C, the head temperature is 230°C, and the screw speed is 200-300r / min.
[0023] As a further solution of the present invention, the drying temperature after granulation is 100° C. and the drying time is 4 hours.
[0024] In a third aspect, the present invention provides an application of a high-performance PPO / POK alloy material in the fields of automotive instrument panels, pipes, valves, gears and bearings.
[0025] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention provides a high-performance PPO / POK alloy material, wherein the carbonyl group of POK undergoes bromination addition under alkaline conditions to connect the styrene monomer to the side chain of POK; and then PS is grafted on the surface of POK through free radical polymerization. Since PPO and PS have good interface interaction, the compatibility of POK and PPO is improved, and the comprehensive performance of the PPO / POK alloy is improved.
[0026] 2. The compatibility of the PPO / POK alloy prepared by the present invention is improved, giving the alloy material excellent strength and toughness, as well as higher chemical resistance, heat resistance and wear resistance, avoiding the problems of reduced strength and heat resistance, increased water absorption and the like of PS or PA modified PPO, and broadening its application in automobile dashboards, pipelines, valve corrosion-resistant parts, gears and bearing wear-resistant parts. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The present invention will be further described below in conjunction with the accompanying drawings.
[0028] Figure 1 is a preparation flow chart of PS-g-POK resin prepared in Preparation Example 1 of the present invention; Figure 2This is an infrared test characterization diagram of the PS-g-POK resin prepared in Preparation Example 1 of the present invention; Figure 3 yes Figure 2 The corresponding enlarged image of region 1 in the middle; Figure 4 yes Figure 2 The corresponding enlarged image of area 2 in the middle; Figure 5 yes Figure 2 The corresponding enlarged image of area 3 in the middle. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Obviously, the following descriptions are only some examples or embodiments of the present application. For ordinary technicians in this field, the present application can also be applied to other similar scenarios without creative work. In addition, it can also be understood that although the efforts made in this development process may be complicated and lengthy, for ordinary technicians in the field related to the content disclosed in this application, some changes in design, manufacturing or production based on the technical content disclosed in this application are just conventional technical means, and should not be understood as insufficient content disclosed in this application.
[0031] However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially the same structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the following description is provided for those skilled in the art to fully understand the present application and is not intended to limit the subject matter described in the claims.
[0032] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution, and all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0034] Any range described in the present invention includes the end value and any numerical value between the end values and any sub-range formed by the end value or any numerical value between the end values.
[0035] Preparation Example 1
[0036] See also Figure 1 The preparation flow chart shown in the figure, this preparation example provides a PS-g-POK resin, which is prepared by the following steps: Raw material weighing and preparation: 10g POK resin (Hyosung, brand M630); 90g CPL; 1g tBuOK, using deionized water as solvent, prepared into 88.5mL 0.1M tBuOK solution; 20g 4-bromostyrene, using ethanol as solvent, prepared into 218mL 0.5M 4-bromostyrene solution; 0.2g AIBN; 1g styrene; S1. Caprolactam dissolution: 90 g of CPL was added to a round-bottom flask and heated to 140 ° C to melt it. Using CPL as a solvent, 10 g of POK resin was dissolved in CPL at a stirring speed of 100 r / min to obtain a uniformly mixed POK / CPL solution; S2. Bromination reaction grafting: Under nitrogen and stirring speed of 50r / min, add 88.5mL of 0.1M tBuOK solution to the POK / CPL solution. With the addition of strong base, the solution color turns black. Continue stirring and reacting at 140°C for 3h. Then add 218mL of 0.5M 4-bromostyrene solution, continue stirring and reacting for 6h, cool to 100°C, and remove excess 4-bromostyrene in vacuo to obtain an intermediate product. S3. Styrene grafting polymerization: At a temperature of 100°C and nitrogen, 0.2 g AIBN and 1 g styrene were added to the intermediate product, and the reaction was stirred at a speed of 100 r / min for 8 h. The product was precipitated with a mixed solvent of water and ethanol (v / v=1:1), filtered and washed with the mixed solvent for 3 times, and then vacuum dried at 60°C to obtain PS-g-POK resin.
[0037] The prepared PS-g-POK resin was characterized and tested. It was purified before the test. The PS-g-POK grafted product was purified by Soxhlet extraction using tetrahydrofuran as solvent to remove self-polymerized polystyrene. After vacuum drying, it was pressed into tablets by a vulcanizer and subjected to ATR infrared testing. The characterization test results of PS-g-POK resin and ungrafted POK resin were compared. Figure 2 As shown; in order to facilitate the observation of the differences in infrared characteristic peaks, area 1, area 2 and area 3 in the spectrum are enlarged.
[0038] Figure 2The enlarged image corresponding to area 1 is Figure 3 ,Depend on Figure 3 It can be seen that: at 3081cm -1 , 3059cm -1 and 3027cm -1 Characteristic peaks appear, corresponding to the stretching vibration of CH of the benzene ring; Figure 2 The enlarged image corresponding to area 2 is Figure 4 ,Depend on Figure 4 It can be seen that at 1062cm -1 , 1493cm -1 and 1453cm -1 Characteristic peaks appear, corresponding to the stretching vibration of C=C on the benzene ring; Figure 2 The enlarged image corresponding to area 3 is Figure 5 ,Depend on Figure 5 It can be seen that: at 759cm -1 and 698cm -1 Characteristic peaks appear, corresponding to the in-plane bending vibration of the monosubstituted benzene ring CH.
[0039] The above characteristic peaks indicate that POK and PS form a grafted structure.
[0040] Preparation Example 2
[0041] This preparation example provides a preparation method of PS-g-POK resin. The difference from Preparation Example 1 is that the POK resin is M330 produced by Hyosung, and the remaining steps and parameters are the same as those in Preparation Example 1.
[0042] Example 1
[0043] A high-performance PPO / POK alloy material, comprising the following components in parts by weight: PPO resin (Bluestar, brand LXR-040) 70 parts; PS-g-POK resin (prepared in Preparation Example 1) 5 parts; POK resin (Hyosung, brand M630) 15 parts; Antioxidant 1010 0.2 parts, antioxidant 168 0.2 parts; 0.1 part of ethylene bisstearamide; The preparation method of the PPO / POK alloy material comprises the following steps: The components were weighed according to the above-mentioned weight proportions, and the mixture was blended and modified by a twin-screw extruder. The feeding section temperature of the twin-screw extruder was 200°C, the compression section temperature was 210°C, the metering section temperature was 230°C, the die head temperature was 230°C, and the screw speed was 250 r / min. After cooling, cutting, and granulation, the particles were dried at 100°C for 4 hours to obtain a PPO / POK alloy material.
[0044] Example 2
[0045] A high-performance PPO / POK alloy material, comprising the following components in parts by weight: PPO resin (Bluestar, brand LXR-040) 70 parts; PS-g-POK resin (prepared in Preparation Example 1) 10 parts; POK resin (Hyosung, brand M630) 20 parts; Antioxidant 1010 0.2 parts, antioxidant 168 0.2 parts; 0.1 part of ethylene bisstearamide; The preparation method of the PPO / POK alloy material comprises the following steps: The components were weighed according to the above-mentioned weight proportions, and the mixture was blended and modified by a twin-screw extruder. The feeding section temperature of the twin-screw extruder was 200°C, the compression section temperature was 210°C, the metering section temperature was 230°C, the die head temperature was 230°C, and the screw speed was 250 r / min. After cooling, cutting, and granulation, the particles were dried at 100°C for 4 hours to obtain a PPO / POK alloy material.
[0046] Example 3
[0047] A high-performance PPO / POK alloy material, comprising the following components in parts by weight: PPO resin (Bluestar, brand LXR-040) 70 parts; PS-g-POK resin (prepared in Preparation Example 2) 10 parts; POK resin (Hyosung, brand M330) 20 parts; Antioxidant 1010 0.2 parts, antioxidant 168 0.2 parts; 0.1 part of ethylene bisstearamide; The preparation method of the PPO / POK alloy material comprises the following steps: The components were weighed according to the above-mentioned weight proportions, and the mixture was blended and modified by a twin-screw extruder. The feeding section temperature of the twin-screw extruder was 200°C, the compression section temperature was 210°C, the metering section temperature was 230°C, the die head temperature was 230°C, and the screw speed was 250 r / min. After cooling, cutting, and granulation, the particles were dried at 100°C for 4 hours to obtain a PPO / POK alloy material.
[0048] Example 4
[0049] A high-performance PPO / POK alloy material, comprising the following components in parts by weight: PPO resin (Bluestar, brand LXR-040) 65 parts; PS-g-POK resin (prepared in Preparation Example 1) 15 parts; POK resin (Hyosung, brand M630) 20 parts; Antioxidant 1010 0.2 parts, antioxidant 168 0.2 parts; 0.1 part of ethylene bisstearamide; The preparation method of the PPO / POK alloy material comprises the following steps: The components were weighed according to the above-mentioned weight proportions, and the mixture was blended and modified by a twin-screw extruder. The feeding section temperature of the twin-screw extruder was 200°C, the compression section temperature was 210°C, the metering section temperature was 230°C, the die head temperature was 230°C, and the screw speed was 250 r / min. After cooling, cutting, and granulation, the particles were dried at 100°C for 4 hours to obtain a PPO / POK alloy material.
[0050] Example 5
[0051] A high-performance PPO / POK alloy material, comprising the following components in parts by weight: PPO resin (Bluestar, brand LXR-040) 50 parts; PS-g-POK resin (prepared in Preparation Example 1) 20 parts; POK resin (Hyosung, brand M630) 10 parts; Antioxidant 1010 0.2 parts, antioxidant 168 0.2 parts; 0.1 part of ethylene bisstearamide; The preparation method of the PPO / POK alloy material comprises the following steps: The components were weighed according to the above-mentioned weight proportions, and the mixture was blended and modified by a twin-screw extruder. The feeding section temperature of the twin-screw extruder was 200°C, the compression section temperature was 210°C, the metering section temperature was 230°C, the die head temperature was 230°C, and the screw speed was 250 r / min. After cooling, cutting, and granulation, the particles were dried at 100°C for 4 hours to obtain a PPO / POK alloy material.
[0052] Example 6
[0053] A high-performance PPO / POK alloy material, comprising the following components in parts by weight: PPO resin (Bluestar, brand LXR-040) 80 parts; PS-g-POK resin (prepared in Preparation Example 1) 15 parts; POK resin (Hyosung, brand M630) 5 parts; Antioxidant 1010 0.2 parts, antioxidant 168 0.2 parts; 0.1 part of ethylene bisstearamide; The preparation method of the PPO / POK alloy material comprises the following steps: The components were weighed according to the above-mentioned weight proportions, and the mixture was blended and modified by a twin-screw extruder. The feeding section temperature of the twin-screw extruder was 200°C, the compression section temperature was 210°C, the metering section temperature was 230°C, the die head temperature was 230°C, and the screw speed was 250 r / min. After cooling, cutting, and granulation, the particles were dried at 100°C for 4 hours to obtain a PPO / POK alloy material.
[0054] Comparative Example 1
[0055] A PPO / POK alloy material, comprising the following components in parts by weight: PPO resin (Bluestar, brand LXR-040) 70 parts; PS resin (grade 525) 10 parts; POK resin (Hyosung, brand M630) 20 parts; Antioxidant 1010 0.2 parts, antioxidant 168 0.2 parts; 0.1 part of ethylene bisstearamide; The preparation method of the PPO / POK alloy material comprises the following steps: The components were weighed according to the above-mentioned weight proportions, and the mixture was blended and modified by a twin-screw extruder. The feeding section temperature of the twin-screw extruder was 200°C, the compression section temperature was 210°C, the metering section temperature was 230°C, the die head temperature was 230°C, and the screw speed was 250 r / min. After cooling, cutting, and granulation, the particles were dried at 100°C for 4 hours to obtain a PPO / POK alloy material.
[0056] Comparative Example 2
[0057] A PPO / POK alloy material, comprising the following components in parts by weight: PPO resin (Bluestar, brand LXR-040) 70 parts; PS resin (Yangzi Petrochemical, brand GP-525) and POK resin (Hyosung, brand M630) were mixed in a mass ratio of 1:1, 10 parts of resin; POK resin (Hyosung, brand M630) 20 parts; Antioxidant 1010 0.2 parts, antioxidant 168 0.2 parts; 0.1 part of ethylene bisstearamide; The preparation method of the PPO / POK alloy material comprises the following steps: The components were weighed according to the above-mentioned weight proportions, and the mixture was blended and modified by a twin-screw extruder. The feeding section temperature of the twin-screw extruder was 200°C, the compression section temperature was 210°C, the metering section temperature was 230°C, the die head temperature was 230°C, and the screw speed was 250 r / min. After cooling, cutting, and granulation, the particles were dried at 100°C for 4 hours to obtain a PPO / POK alloy material.
[0058] Comparative Example 3
[0059] A high-performance PPO / POK alloy material, comprising the following components in parts by weight: PPO resin (Bluestar, brand LXR-040) 70 parts; PS-g-POK resin (prepared in Preparation Example 1) 1 part; POK resin (Hyosung, brand M630) 20 parts; Antioxidant 1010 0.2 parts, antioxidant 168 0.2 parts; 0.1 part of ethylene bisstearamide; The preparation method of the PPO / POK alloy material comprises the following steps: The components were weighed according to the above-mentioned weight proportions, and the mixture was blended and modified by a twin-screw extruder. The feeding section temperature of the twin-screw extruder was 200°C, the compression section temperature was 210°C, the metering section temperature was 230°C, the die head temperature was 230°C, and the screw speed was 250 r / min. After cooling, cutting, and granulation, the particles were dried at 100°C for 4 hours to obtain a PPO / POK alloy material.
[0060] Comparative Example 4
[0061] A high-performance PPO / POK alloy material, comprising the following components in parts by weight: PPO resin (Bluestar, brand LXR-040) 70 parts; PS-g-POK resin (prepared in Preparation Example 1) 25 parts; POK resin (Hyosung, brand M630) 20 parts; Antioxidant 1010 0.2 parts, antioxidant 168 0.2 parts; 0.1 part of ethylene bisstearamide; The preparation method of the PPO / POK alloy material comprises the following steps: The components were weighed according to the above-mentioned weight proportions, and the mixture was blended and modified by a twin-screw extruder. The feeding section temperature of the twin-screw extruder was 200°C, the compression section temperature was 210°C, the metering section temperature was 230°C, the die head temperature was 230°C, and the screw speed was 250 r / min. After cooling, cutting, and granulation, the particles were dried at 100°C for 4 hours to obtain a PPO / POK alloy material.
[0062] The relevant parameters in the above embodiments and comparative examples are summarized in Table 1.
[0063] Table 1
[0064] Performance Testing: The PPO / POK alloy materials prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were injection molded into mechanical property test specimens using a plastic injection machine to perform mechanical property tests: (1) Tensile properties shall comply with GB / T 1040 standard; (2) Bending properties shall comply with GB / T 9341; (3) Notch impact test is conducted in accordance with GB / T 1843; The number of tests for each spline is 5, and the average value is taken as the result of the group.
[0065] The above test results are shown in Table 2.
[0066] Table 2
[0067] (4) Water absorption test is based on ISO 62 standard, and is placed at 23°C and 50% RH for 24 hours; (5) The thermal deformation temperature is in accordance with GB / T 1634.2. The load is applied so that the maximum normal bending stress of the specimen reaches 1.82 MPa. The temperature at which the relative change in the midpoint deflection of the specimen before and after heating reaches 0.25 mm is taken as the thermal deformation temperature of the specimen. (6) For resistance to solvent corrosion, use medical gauze saturated with solvent to wipe the same place on the surface of the specimen 200 times with the same pressure, and calculate the mass loss rate; (7) Flame retardant performance refers to UL94 test method; The above test results are shown in Table 3.
[0068] Table 3
[0069] As can be seen from Table 2 and Table 3, in Comparative Example 2 and Comparative Example 1, the PS-g-POK resin is completely replaced by the PS resin. Although the PS resin and the PPO resin have a good interface interaction, the PS resin is not grafted with the POK resin, and it does not improve the compatibility between the PPO resin and the POK resin, resulting in poor performance of the PPO / POK alloy; in Comparative Example 2 and Comparative Example 2, the PS-g-POK resin is replaced by a mixed resin of PS and POK. Since the compatibility problem between PS and POK is not solved, the PPO / POK alloy material still maintains poor performance; in Comparative Example 2 and Comparative Example 3 and Comparative Example 4, the amount of PS-g-POK resin is reduced, and the performance of the PPO / POK alloy material is poor. Increasing the amount of PS-g-POK resin can also keep the performance of the PPO / POK alloy material relatively stable. In order to reduce the preparation cost of the PPO / POK alloy material, the PS-g-POK resin in the present invention is used in a ratio of 5-20 parts by weight, which can not only achieve better alloy material performance, but also achieve cost reduction and efficiency improvement.
[0070] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0071] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high performance PPO / POK alloy material, characterized in that: According to parts by weight, it includes the following components: PPO resin 50-80 parts; PS-g-POK resin 5-20 parts; 5-20 parts of POK resin; Antioxidant 0.1-1 part; Lubricant 0.1-1 part.
2. A high performance PPO / POK alloy material according to claim 1, characterized in that: The PS-g-POK resin is prepared by the following steps: S1. Dissolve the POK resin in CPL at a temperature of 135-145°C, mix well, and obtain a POK / CPL solution; S2. Under nitrogen and stirring conditions, add a strong base solution to the POK / CPL solution and react at 135-145°C for 2-4 hours; then add 4-bromostyrene solution and continue to react for 5-7 hours to obtain an intermediate product; S3. Add AIBN and styrene to the intermediate product at a temperature of 95-105°C and nitrogen, stir and react for 7-9 hours, collect the product, and obtain PS-g-POK resin after drying.
3. A high performance PPO / POK alloy material according to claim 2, characterized in that: In S1, the mass ratio of POK resin to CPL is 10:
90.
4. A high performance PPO / POK alloy material according to claim 2, characterized in that: In S2, the concentration of the strong base solution is 0.1 M, and the strong base is any one of potassium tert-butoxide and sodium ethoxide; The mass ratio of POK to strong base in the POK / CPL solution is 10:
1.
5. A high performance PPO / POK alloy material according to claim 2, characterized in that: In S2, the concentration of the 4-bromostyrene solution is 0.5 M, and the solvent of the 4-bromostyrene solution is ethanol or dimethyl sulfoxide; The mass ratio of POK to 4-bromostyrene in the POK / CPL solution is 1:
2.
6. A high performance PPO / POK alloy material according to claim 2, characterized in that: In S3, the mass ratio of AIBN to POK in the intermediate product is 0.01-0.1:
1.
7. A high performance PPO / POK alloy material according to claim 2, characterized in that: In S3, the mass ratio of styrene to POK in the intermediate product is 0.1:
1.
8. A method for preparing a high-performance PPO / POK alloy material as claimed in claim 1, characterized in that: The following steps are involved: The components are weighed according to their weight proportions, blended and modified by a twin-screw extruder, and dried after cooling, cutting, granulation, to obtain a PPO / POK alloy material.
9. The method for preparing a high-performance PPO / POK alloy material according to claim 8, characterized in that: The feeding section temperature of the screw of the twin-screw extruder is 200°C, the compression section temperature is 200-220°C, the metering section temperature is 220-240°C, the die head temperature is 230°C, and the screw speed is 200-300r / min.
10. Application of the high performance PPO / POK alloy material as claimed in claim 1 in automobile instrument panels, pipes, valves, gears and bearings.
Citation Information
Patent Citations
A low dielectric lightweight PPO / POK composite material and preparation method thereof
CN117089191B
Low-warpage and high-hardness polymer and preparation method thereof
CN105400173A
Polyphenylether / polyketone composite material and preparation method thereof
CN108517109A
Ultrahigh-flow high-impact PPO / PA66 alloy material and preparation method thereof
CN113604038A
Polyphenyl ether / nylon 56 / polyketone alloy material and preparation method thereof
CN115197559A